An Update on the Content of Fatty Acids, Dioxins, PCBs and Heavy Metals in Farmed, Escaped and Wild Atlantic Salmon (Salmo salar L.) in Norway - Ida-Johanne Jensen; Karl-Erik Eilertsen; Carina Helen Almli Otnæs; Hanne K. Mæhre; Edel Oddny Elvevoll (Foods, 2020)
In this paper, we present updated data on proximate composition, amino acid, and fatty acid composition, as well as concentrations of dioxins, polychlorinated biphenyls (PCBs), and selected heavy metals, in fillets from farmed (n = 20), escaped (n = 17), and wild (n = 23) Atlantic salmon (Salmo salar L.). The concentrations of dioxins (0.53 ± 0.12 pg toxic equivalents (TEQ)/g), dioxin-like PCBs (0.95 ± 0.48 pg TEQ/g), mercury (56.3 ± 12.9 µg/kg) and arsenic (2.56 ± 0.87 mg/kg) were three times higher in wild compared to farmed salmon, but all well below EU-uniform maximum levels for contaminants in food. The six ICES (International Council for the Exploration of the Sea) PCBs concentrations (5.09 ± 0.83 ng/g) in wild salmon were higher than in the farmed fish (3.34 ± 0.46 ng/g). The protein content was slightly higher in wild salmon (16%) compared to the farmed fish (15%), and the amount of essential amino acids were similar. The fat content of farmed salmon (18%) was three times that of the wild fish, and the proportion of marine long-chain omega-3 fatty acids was a substantially lower (8.9 vs. 24.1%). The omega-6 to omega-3 fatty acid ratio was higher in farmed than wild salmon (0.7 vs. 0.05). Both farmed and wild Atlantic salmon are still valuable sources of eicosapentaenoic acid and docosahexaenoic acid. One 150 g portion per week will contribute to more (2.1 g and 1.8 g) than the recommended weekly intake for adults.